2017
DOI: 10.3892/ol.2017.5877
|View full text |Cite
|
Sign up to set email alerts
|

Gene and miRNA expression profiles of mouse Lewis lung carcinoma LLC1 cells following single or fractionated dose irradiation

Abstract: In clinical practice ionizing radiation (IR) is primarily applied to cancer treatment in the form of fractionated dose (FD) irradiation. Despite this fact, a substantially higher amount of current knowledge in the field of radiobiology comes from in vitro studies based on the cellular response to single dose (SD) irradiation. In addition, intrinsic and acquired resistance to IR remains an issue in clinical practice, leading to radiotherapy treatment failure. Numerous previous studies suggest that an improved u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…The current study investigated the effects of cryptotanshinone on a number of miRNAs. miRNA expression analysis was performed following 6 h of treatment, while protein expression analysis was performed following 24 h of treatment as alterations in miRNA expression levels have been reported to occur at a faster rate compared with alterations in protein expression levels (20). It was identified that the expression levels of the following miRNAs were significantly altered following treatment with cryptotanshinone: miR-30d-5p, miR-126-3p, miR-133a, miR-338-3p, miR-451a, miR-21-5p, miR-96-5p, miR-182-5p and miR-205-5p.…”
Section: Discussionmentioning
confidence: 99%
“…The current study investigated the effects of cryptotanshinone on a number of miRNAs. miRNA expression analysis was performed following 6 h of treatment, while protein expression analysis was performed following 24 h of treatment as alterations in miRNA expression levels have been reported to occur at a faster rate compared with alterations in protein expression levels (20). It was identified that the expression levels of the following miRNAs were significantly altered following treatment with cryptotanshinone: miR-30d-5p, miR-126-3p, miR-133a, miR-338-3p, miR-451a, miR-21-5p, miR-96-5p, miR-182-5p and miR-205-5p.…”
Section: Discussionmentioning
confidence: 99%
“…After the mice had been acclimated for one week, 1 × 10 5 LLC cells resuspended in 0.1 mL phosphate-buffered saline (PBS) were subcutaneously implanted into the right groin [ 16 ]. Tumor dimensions were measured by digital calipers at days 7, 10, 14, 17, and 21 ( Figure 1(a) ), and the tumor volume (mm 3 ) was calculated as follows: (length × width 2 )/2 [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Brachytherapy needles were purchased from IZI Medical Products (MD, USA) for the intra-tumoral administration of the SRBs. The lung (LLC1) mouse cancer cells (ATCC, USA) were cultured based on standard reported protocols ( 19 ). The monoclonal antibody anti-mouse CD40 (FGK4.5/FGK45) was bought from BioXcell (New-Hampshire, USA).…”
Section: Methodsmentioning
confidence: 99%
“…to serve as multifunctional SRBs. These SRBs can help ensure geometric accuracy during treatment, but also deliver immunoadjuvants to boost the abscopal response ( 18 , 19 ), all at no additional inconvenience to cancer patients ( 2 , 8 , 13 ).…”
Section: Introductionmentioning
confidence: 99%